Tipping points in international law : commitment and critique - Tipping Points in International Law (Conference) (2019 : Washington, D.C.); Haskell, John (John D.); D'Aspremont, Jean (Cambridge : Cambridge University Press, 2021)
Addressing some of the most perilous, controversial issues in international law and governance, this volume brings together legal scholars from diverse geographic, personal and scholarly perspectives. They reflect on the pervasive feeling of crisis in the world today and share their views on the possibilities and limits of the international legal architecture and its expert communities in shaping the world of tomorrow. What exactly is this feeling that the contemporary international legal architecture is at a tipping point? What do these possible risks expose about the fragility and limits of our current conceptual and institutional order? What commitments drive our hopes and anxieties? Authors explore these questions across a wide range of possible tipping points and offer readers a unique snapshot of the lived experience of what it means to be an expert engaged right now in international law and governance. Each chapter covers both theory and practice in analysing a current problem.
Title from publisher's bibliographic system (viewed on 25 Oct 2021).
Keywords: International law -- Congresses